The Important Roles of Ecomychorizae to Increase Growth Rate of Sacha Inchi (Plukenetia volubilis L.) that Potentially as Raw Material of Biofuel - Rosnina A.G; Zurrahmi Wirda; M. Hadid Al Hafizh (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
Recently the use of agricultural waste containing cellulose and lignin as an alternative fuel that is environmentally friendly. The study aimed to determine the important roles of eco-enzymes and mycorrhizae due to increasing the growth rate of sacha inchi plants that are tolerant to nutrient-poor soils such as Inceptisol which are classified as sub-optimal lands. Sacha inchi broadleaf plants are classified as having a high lignin content due to their biomass potentially producing alternative fuels that can reduce dependence on the use of fossils, which were decreasing. This research was conducted in West Reuleut Village, Muara Batu District, North Aceh District and the Laboratory of the Faculty of Agriculture, Malikussaleh University. This research was carried out from April to August 2022.The Application of eco-enzymes on Inceptisol soil has increased the absorption of several macronutrients that were impacted by the fresh weight of the root, root dry weight, and root length of sacha inchi. The activities of eco enzyme and mycorrhizae which were giving a positive impact on the vegetative growth rate of Sacha inchi plants. Eco enzymes contain microorganisms that help the process of decomposition, transport of nutrients, and mycorrhizae as biological fertilizers that can provide nutrient uptake for plants. The impact of synergizing both fertilizers together has increased the suitability and productivity of sub-optimal soil that is able to increase growth and yield plant. The increasing productivity of Sacha inchi plants which contain lignin and cellulose also increases plant biomass which has the potential to produce high bioethanol as well.